Dynamics of Divorce Suits In Sambas and Its Implications For The Judicial System in The Sambas Religious Court, West Kalimantan, Indonesia-Malaysia - Asman Asman; Mohamed Aamer; Asmak Asmak; Khairuddin Khairuddin (Abdurrauf Law and Sharia, 2026)
This research is motivated by the high number of divorce cases filed by wives against their husbands at the Sambas Religious Court, a socio-legal phenomenon indicating significant changes in contemporary Muslim family relations. This increase not only reflects internal household issues but also indicates a growing legal awareness among women in fighting for their rights. The research problem formulation includes the factors causing the increase in divorce cases and their implications for the judicial system, particularly regarding the functional relationship with the Sambas District Court. This study aims to comprehensively analyze the dynamics of divorce cases and assess their impact on the cross-jurisdictional judicial system. The method used is a normative-empirical (socio-legal) approach, with data collection techniques including observation, interviews, and analysis of case decisions. The results indicate that the dominant factors causing divorce cases include economic problems, domestic violence (KDRT), infidelity, and disharmony in marital relationships. Furthermore, this phenomenon has resulted in an increased caseload in the courts, a shift in public perception of the judiciary as a means of protecting women's rights, and the emergence of potential overlapping jurisdictions between the Religious Courts and the District Courts in derivative cases. This study concludes that strengthening mediation mechanisms, improving family development programs, and harmonizing the judicial system are necessary to ensure effective and integrated handling of family cases in Indonesia. [Penelitian ini dilatarbelakangi oleh tingginya jumlah perkara cerai gugat yang diajukan oleh istri terhadap suami di Pengadilan Agama Sambas, yang merupakan fenomena sosio-yuridis yang menunjukkan adanya perubahan signifikan dalam relasi keluarga Muslim kontemporer. Peningkatan tersebut tidak hanya mencerminkan permasalahan internal rumah tangga, tetapi juga mengindikasikan meningkatnya kesadaran hukum perempuan dalam memperjuangkan hak-haknya. Rumusan masalah dalam penelitian ini meliputi faktor-faktor yang menyebabkan meningkatnya perkara cerai gugat serta implikasinya terhadap sistem peradilan, khususnya terkait hubungan fungsional dengan Pengadilan Negeri Sambas. Penelitian ini bertujuan untuk menganalisis secara komprehensif dinamika perkara cerai gugat dan menilai dampaknya terhadap sistem peradilan lintas yurisdiksi. Metode yang digunakan adalah pendekatan normatif-empiris (socio-legal), dengan teknik pengumpulan data berupa observasi, wawancara, dan analisis terhadap putusan perkara. Hasil penelitian menunjukkan bahwa faktor-faktor dominan yang menyebabkan terjadinya cerai gugat meliputi permasalahan ekonomi, kekerasan dalam rumah tangga (KDRT), perselingkuhan, serta disharmoni dalam hubungan perkawinan. Selain itu, fenomena ini berdampak pada meningkatnya beban perkara di pengadilan, terjadinya pergeseran persepsi masyarakat terhadap lembaga peradilan sebagai sarana perlindungan hak-hak perempuan, serta munculnya potensi tumpang tindih kewenangan antara Pengadilan Agama dan Pengadilan Negeri dalam perkara-perkara turunan. Penelitian ini menyimpulkan bahwa penguatan mekanisme mediasi, peningkatan program pembinaan keluarga, serta harmonisasi sistem peradilan diperlukan untuk menjamin penanganan perkara keluarga yang efektif dan terintegrasi di Indonesia.]